A larger role for the hearing officer: a modest proposal. (11th January 2018) - Calvani, Terry; Leahy, Jenny
Abstract: This article proposes changes to the role of the EU hearing officer and looks, as a starting point, to the US administrative model, in particular the role of the Administrative Law Judge. It is argued that the US model makes better use of its hearing examiners to understand and probe contested points of fact or law. The article sets out a proposal for strengthening the function and responsibilities of the EU hearing officer to also include a review of substantive points of the case. The hearing officer's substantive findings, in addition to reporting on procedure, would be included in a final public report. These relatively modest changes would provide comfort to the parties that some independent scrutiny of disputed facts had taken place whilst the Commission would retain full discretion as to the ultimate decision. However, importantly, the Commission's decision-making would be aided by a more robust oral hearing. No fundamental changes to the EU's administrative model would be required for the implementation of this proposal. For practical reasons it is suggested to trial this proposal first in the Commission's Article 101 and 102 TFEU investigations.